Precise Localization and Control of Catalytic Janus Micromotors Using Weak Magnetic Fields. (14th January 2015) - Khalil, Islam S. M.; Magdanz, Veronika; Sanchez, Samuel; Schmidt, Oliver G.; Misra, Sarthak
We experimentally demonstrate the precise localization of spherical Pt-Silica Janus micromotors (diameter 5 μm) under the influence of controlled magnetic fields. First, we control the motion of the Janus micromotors in two-dimensional (2D) space. The control system achieves precise localization within an average region-of-convergence of 7 μm. Second, we show that these micromotors provide sufficient propulsion force, allowing them to overcome drag and gravitational forces and move both downwards and upwards. This propulsion is studied by moving the micromotors in three-dimensional (3D) space. The micromotors move downwards and upwards at average speeds of 19.1 μm/s and 9.8 μm/s, respectively. Moreover, our closed-loop control system achieves localization in 3D space within an average region-of-convergence of 6.3 μm in diameter. The precise motion control and localization of the Janus micromotors in 2D and 3D spaces provides broad possibilities for nanotechnology applications.